Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/jctb.1425
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Cd(II) removal from aqueous solutions by adsorption on a highly mineralized peat. Batch and fixed‐bed column experiments

Abstract: This paper evaluates the potential use of a locally available organic soil amendment as a low-cost adsorbent. The removal of cadmium from aqueous solutions was studied by means of kinetic, batch and fixed-bed experiments. Batch experiments were conducted to evaluate the process kinetics and the removal equilibrium over a broad pH range. Pseudo-second-order kinetics and Freundlich equilibrium parameters were obtained. Six column experiments were carried out at different flow-rates and feed concentrations. Break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
(20 reference statements)
1
14
1
Order By: Relevance
“…The statistical data have shown a fair goodness of correlation for pseudo-second-order kinetics (Fig. 5), which were reported previously for heavy metal adsorption by other low-cost adsorbents, such as peat and zeolite for the indication for a potential application in column water treatment [6,16]. After the application of the pseudo-second-order kinetics model, the results were listed in Table 4.…”
Section: Batch Adsorption Kineticssupporting
confidence: 75%
See 2 more Smart Citations
“…The statistical data have shown a fair goodness of correlation for pseudo-second-order kinetics (Fig. 5), which were reported previously for heavy metal adsorption by other low-cost adsorbents, such as peat and zeolite for the indication for a potential application in column water treatment [6,16]. After the application of the pseudo-second-order kinetics model, the results were listed in Table 4.…”
Section: Batch Adsorption Kineticssupporting
confidence: 75%
“…5. As shown from the plot, the major percent of cadmium adsorption process was completed in 8 h as for the different initial concentrations of GRM-cadmium system, which indicate itself a relatively moderate rate to reach adsorption equilibrium [6]. Fig.…”
Section: Batch Adsorption Kineticsmentioning
confidence: 77%
See 1 more Smart Citation
“…Among the above-mentioned processes, adsorption plays a pivotal role in removing metals from the aqueous phase using various biomaterial sorbents, algae (Holan et al 1993), fungi, sugar cane bagasse (Cerino Córdova et al 2011;Peterlene et al 1999), rice husk, wheat barn (Nouri et al 2007), pine bark, olive cake (Doyurum and Celik 2006), coconut husk, chitin (Benguella and Benaissa 2002), ash, activated carbon (Jusoh et al 2007;Onundi et al 2011;Zavvar Mousavi and Seyedi 2011), etc. Clays, zeolite, calcite, manganese nodule residue (Agrawal and Sahu 2006;Tashauoei et al 2010), perlite (Hasan et al 2006) and peat (Gabaldon et al 2006) have also been employed to remove metals from the water phase. Also, low-cost natural clay/soil is used to develop highthroughput inorganic adsorbent as well as membrane filter in removing heavy metals from aqueous phase.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also demonstrated removal capacities in column systems that are different from those predicted from batch equilibrium isotherms. 2,17,31,32 The discrepancies among batch and dynamic sorption data can be attributed to the type of metal-sorbent contact in column experiments, in which the sorbent-to-solution ratio is much higher than in batch mode and the feed solution is continuously pumped, so solutes present in the column are continuously replaced and, at equilibrium, concentration is equal to its respective feed value.…”
Section: Sorption Fixed-bed Experimentsmentioning
confidence: 98%